Ischaemic stroke on anticoagulation therapy and early recurrence in acute cardioembolic stroke: the IAC study. Issue 10 (26th April 2021) - Yaghi, Shadi; Henninger, Nils; Giles, James A; Leon Guerrero, Christopher; Mistry, Eva; Liberman, Ava L; Asad, Daniyal; Liu, Angela; Nagy, Muhammad; Kaushal, Ashutosh; Azher, Idrees; Mac Grory, Brian; et al.
Abstract : Background and purpose: A subset of ischaemic stroke patients with atrial fibrillation (AF) have ischaemic stroke despite anticoagulation. We sought to determine the association between prestroke anticoagulant therapy and recurrent ischaemic events and symptomatic intracranial haemorrhage (sICH). Methods: We included consecutive patients with acute ischaemic stroke and AF from the Initiation of Anticoagulation after Cardioembolic stroke (IAC) study from eight comprehensive stroke centres in the USA. We compared recurrent ischaemic events and delayed sICH risk using adjusted Cox regression analyses between patients who were prescribed anticoagulation (ACp) versus patients who were naïve to anticoagulation therapy prior to the ischaemic stroke (anticoagulation naïve). Results: Among 2084 patients in IAC, 1518 had prior anticoagulation status recorded and were followed for 90 days. In adjusted Cox hazard models, ACp was associated with some evidence of a higher risk higher risk of 90-day recurrent ischaemic events only in the fully adjusted model (adjusted HR 1.50, 95% CI 0.99 to 2.28, p=0.058) but not increased risk of 90-day sICH (adjusted HR 1.08, 95% CI 0.46 to 2.51, p=0.862). In addition, switching anticoagulation class was not associated with reduced risk of recurrent ischaemic events (adjusted HR 0.41, 95% CI 0.12 to 1.33, p=0.136) nor sICH (adjusted HR 1.47, 95% CI 0.29 to 7.50, p=0.641). Conclusion: AF patients with ischaemic stroke despite anticoagulation may have higher recurrent ischaemic event risk compared with anticoagulation-naïve patients. This suggests differing underlying pathomechanisms requiring different stroke prevention measures and identifying these mechanisms may improve secondary prevention strategies.